COMMUNICABLE DISEASES INCIDENCE AND MORTALITY IN THE BELGRADE POPULATION, FROM 2015 TO 2019 - Pajić, Marija; Jovic-Vranes, Aleksandra (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: Communicable diseases remain a significant burden to society, both worldwide and in Serbia. This study aims to analyze the trend of the total number of patients and deaths from communicable diseases in the Belgrade population, in the period 2015 to 2019.Method: A descriptive epidemiological method was used in this study. Morbidity and mortality data related to communicable diseases, taken from the Statistical Reviews of Health Activities in Belgrade issued by the City Institute of Public Health of Belgrade, for the period 2015 – 2019, were used in this study. Data on the number of new patients and deaths from communicable diseases were used, as well as data on the number of new patients, by groups of infectious diseases. Linear regression analysis for trends (curve estimation) was used to estimate trends in morbidity and mortality from infectious diseases during the observed period.Results: A total of 144,215 persons suffering from communicable diseases was registered in Belgrade, from 2015 to 2019. Communicable disease morbidity in the observed period decreased in Belgrade, while communicable disease mortality increased. During that period, there was no statistically significant trend in incidence rates and mortality rates related to communicable diseases (incidence: y = 2,158.120 – 134.000 x, p = 0.073; mortality: y = 4.930 + 0.250 x, p = 0.369). Conclusion: Although highly preventable, communicable diseases are still present in underdeveloped and developed countries. In addition to general and personal hygiene measures, wearing protective masks, avoiding risky behavior and using protection against sexually transmitted diseases, it is also necessary to focus public health measures on environmental protection and the prevention of the spread of infectious agents outside their habitats, as well as on the prevention of the emergence of new infectious agents.
Keywords: communicable diseases; incidence; mortality; trend; public health